IMPACT OF OXIDATIVE STRESS AND ANTIOXIDANT ENZYME ON FERTILITY - EKTA ARPITA ANDRIYAS; SAPNA SMITH LAL (International Journal of Pharma and Bio Sciences, 2016)
Infertility is common health problem and is experienced by many couples now a day. Many studies suggest that oxidative stress is a cause of a range of many pathologic disorders including cancer, cardiovascular disorders, neurogenrative disorders and many of the other thus this study is design to find the effect of oxidative stress on fertility in the females. To achieve this aim 500 married female were included for this study in which 250 were fertile and 250 infertile married females of reproductive age 25-35 yrs having no history of any metabolic disorder. The level of oxidative stress marker Melondialdehyde (MDA) and three antioxidant enzyme catalase (CAT), ceruloplasmin and superoxide dimutase (SOD) were measured. The results of MDA showed a significant (p>0.0001) increase in the MDA level and significant (p>0.0001) decrease in the catalase, ceruloplasmin and SOD in the infertile group when compared to the fertile group. The correlative study between the superoxide and Melondialdehyde indicated (r=-0.53, p<0.05) a significant negative correlation, similarly a significant negative correlation was found among Melondialdehyde and catalase (r=-0.29, p<0.05) as well as in between Melondialdehyde and ceruloplasmin (r=0.20, p<0.05).These results suggest that oxidative stress is related with the pathophysiology of fertility in the females.